2015
DOI: 10.1111/eje.12167
|View full text |Cite
|
Sign up to set email alerts
|

Perceived learned skills and professional development of graduates from a master in dental public health programme

Abstract: IntroductionAssessing the impact of a training programme is important for quality assurance and further development. It also can helps with accountability and marketing purposes. This study evaluated the impact of King's College London (KCL) Master of Science programme in Dental Public Health in terms of graduates' perceived learned skills and professional development.MethodsAn online questionnaire was sent to individuals who completed successfully the KCL Master of Science programme in Dental Public Health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…[ 3 4 5 ] Moreover, it has been reported that stress could affect mental health like anxiety, depression,[ 6 7 ] burnout, and suicide. [ 8 9 10 ] High levels of stress among students could lead to decreased concentration, decreased job satisfaction, and increased proneness to make medical errors. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 5 ] Moreover, it has been reported that stress could affect mental health like anxiety, depression,[ 6 7 ] burnout, and suicide. [ 8 9 10 ] High levels of stress among students could lead to decreased concentration, decreased job satisfaction, and increased proneness to make medical errors. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…The study by Walsh et al, [23] showed that despite being trained, public health graduates lacked critical knowledge and experience to operate under stressful conditions thereby resorting to other comfortable career options. Our study seem to point out some training gaps which could be identified as professional training needs and ploughed back to the graduates' curriculum for better workforce development as suggested by Aslam and team [24].…”
Section: Discussionmentioning
confidence: 59%
“…Documents without a focus on the development and definition of postgraduate DPH competencies were excluded (for example, articles about undergraduate DPH education or DPH's role in clinical interventions). This resulted in 12 citations with available full‐text in English language 15,20,23–28,39–41 . Moreover, four other official documents were identified through a manual search in Google and Google Scholar, which resulted in a total of 16 documents (Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in 12 citations with available full-text in English language. 15,20,[23][24][25][26][27][28][39][40][41] Moreover, four other official documents were identified through a manual search in Google and Google Scholar, which resulted in a total of 16 documents (Appendix A). After a full-text review of the included literature, 11 articles were excluded due to either being outdated or not discussing the development of postgraduate competencies for DPH.…”
Section: Re Sultsmentioning
confidence: 99%